1999
DOI: 10.1080/00288233.1999.9513361
|View full text |Cite
|
Sign up to set email alerts
|

Growth of United States versus New Zealand white clover cultivars in diverse grasses in Mississippi, USA

Abstract: The use of plant material outside the country of development is common, but whether such material is superior to existing types of the same species is questionable. Seven United States and eight New Zealand white clover (Trifolium repens) cultivars, germplasms, or breeding populations were evaluated for plant spread and dry matter yield for two years at Mississippi State, Mississippi, USA, when grown in monoculture or with grasses having differing seasonal growth patterns, viz tall fescue (Festuca arundinacea)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Brink (1995) reported that white clover thrives well under varying environmental conditions in the southeastern USA. In a comparative study of growth of U.S. and New Zealand white clover cultivars, similar reports were made by Pederson et al (1999) that several varieties thrive well in this region of southeastern USA where the climatic extremes vary from season to season but routinely include droughty, hot, humid summers with complete leaf desiccation and cool, wet winters in saturated soils. Genotypic variability is not the only mechanisms by which white clover adapts to specific environments .…”
Section: Adaptationmentioning
confidence: 71%
“…Brink (1995) reported that white clover thrives well under varying environmental conditions in the southeastern USA. In a comparative study of growth of U.S. and New Zealand white clover cultivars, similar reports were made by Pederson et al (1999) that several varieties thrive well in this region of southeastern USA where the climatic extremes vary from season to season but routinely include droughty, hot, humid summers with complete leaf desiccation and cool, wet winters in saturated soils. Genotypic variability is not the only mechanisms by which white clover adapts to specific environments .…”
Section: Adaptationmentioning
confidence: 71%
“…Local adaptation is important, as shown by the poor performance of many foreign cultivars in the study by Pederson et al (1999). There are notable cases, however, in which foreign cultivars have made excellent parents when combined with local ecotypes (Bouton et al, 2005).…”
Section: White Clovermentioning
confidence: 95%
“…Varieties bred in one country may not always perform well in another. For example, Brink et al (1999) describe the very different environment and therefore variety requirements in the south-eastern USA and Pederson et al (1999) demonstrated the superiority of white clover varieties bred in the USA over New Zealand varieties, when evaluated in the USA.…”
Section: Breeding Targetsmentioning
confidence: 99%